Managing Native Vegetation for Wildlife - Rick Williams; Tim Baxley (EDIS)
FOR-186, a 5-page illustrated fact sheet by Rick Williams and Tim Baxley, discusses key plants that are beneficial to several species of wildlife, and how to manage them to improve the quality of forage available to wildlife. Includes references. Published by the UF School of Forest Resources and Conservation, June 2008.